Digital energy visualisations in the workplace: the e-Genie tool - Spence, Alexa; Goulden, Murray; Leygue, Caroline; Banks, Nick; Bedwell, Benjamin D.; Jewell, Mike; Yang, Rayoung; Ferguson, Eamonn (Taylor & Francis, 2017)
Building management systems are designed for energy managers; there are few energy feedback systems designed to engage staff. A tool, known as e-Genie, was developed to engage workplace occupants with energy data and support them to take action to reduce energy use. Building on research insights within the field, e-Genie’s novel approach encourages users to make plans to meet energy saving goals, supports discussion, and considers social energy behaviours (e.g. discussing energy issues, taking part in campaigns) as well as individual actions. A field based study of e-Genie indicated that visualisations of energy data were engaging and that the discussion ‘Pinboard’ was particularly popular. Pre- and post survey (N = 77) evaluation of users indicated that people were significantly more concerned about energy issues and reported engaging more in social energy behaviour after ~two weeks of e-Genie being installed. Concurrently, objective measures of electricity use decreased over the same period, and continued decreasing over subsequent weeks. Indications are that occupant facing energy feedback visualisations can be successful in reducing energy use in the workplace; furthermore supporting social energy behaviour in the workplace is likely to be a useful direction for promoting action.